Application research of shortening delivery time through value stream mapping analysis - Guo-qiang Pan; Ding-zhong Feng; Mei-xian Jiang (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
Value stream mapping is a kind of technique that helps to understand and streamline production processes. With a case study of a metal machinery factory, the production process path is visualized by mapping the current state value stream. After tracking the production process of a medium-sized order, problems affecting the delivery time are identified and its causes analyzed. A future state value stream map is created and an optimization scheme is suggested, with which the production cycle of the order is expected to be shortened from 21 days to 9 days, representing a 57% reduction. Value stream mapping is proved as a useful technique to shorten delivery time and reduce production costs.